Farmers’ perception on the performance of different rice varieties in Kapilvastu district, Nepal - Sapkota, Sundar; Sapkota, Sanjib (Journal of Agriculture and Natural Resources, 2020)
Rice is the major staple food crop in Nepal. To date, several rice varieties have been developed and released in Nepal. However, rice production is far below in comparison with its production potential. A household survey was conducted in Bangaganga municipality of Kapilvastu district in 2018 to assess farmers’ perception on performance of four different rice varieties (Radha-4, Ramdhan, Gorakhnath, and Sawa). The data were collected from a total of 120 rice farmers (randomly selected) using the interview schedule and analyzed using descriptive statistics, Likert scale, and indexing technique. Statistical analysis showed that the Ramdhan variety had the highest yield (4.95 t/ha), whereas Radha-4 had the lowest yield (3.15 t/ha). The most disease and drought-tolerant variety, as perceived by the farmers, was Radha-4. Smut and Khaira were perceived as the primary diseases whereas Brown planthopper and Rice Gundhi bug were the most important insects of all studied rice varieties. The study recommended that the plant breeders should focus on developing site-specific rice varieties to meet the multiple concerns of the farmers, such as higher yield and stress-tolerant. The farmers should be made aware of varietal selection and crop pest management techniques via training programs, which further helps to reduce the yield gap between farmers’ field and research field.